THE EFFECTIVENESS OF USING AUTHENTIC MATERIALS IN TEACHING DESCRIPTIVE TEXT TO IMPROVE STUDENTS' SPEAKING ABILITY(AN EXPERIMENTAL STUDY AMONG THE TENTH GRADE STUDENTS OF SENIOR HIGH SCHOOL) - Mira Agustina, - (2009)
The use of authentic materials in an EFL classroom has been discussed by many teachers in foreign language teaching in recent years. Thus, this research was aimed at finding out the effectiveness of using authentic materials in teaching descriptive text to improve students' speaking ability. This study adopted the quasi-experimental method with the non-equivalent control group design. This study involved 66 students at SMA PGRI Cicalengka, which divided into two groups: experimental group and control group. Pretest, treatment and posttest served as the research design in this study. Speaking test, questionnaire and interview were used as the research instrument. The result of pretest and posttest were analyzed by using SPSS 15.00 version whereas the result of questionnaire was analyzed by using percentage and the result of interview was transcribed and classified to get additional information. The result of the study indicated that the means of posttest score of experimental group was significantly higher than that for the control group. In addition, from the analysis of pretest and posttest scores of experimental group, it was found that authentic materials improve students' speaking ability especially in grammar and vocabulary mastery. The data obtained from questionnaire and interview also showed that the use of authentic materials was effective in teaching descriptive text to improve students' speaking ability because authentic materials made learning activities more comprehensible, fun and interesting. The research finding was expected to give positive and useful contribution in English teaching learning process.